Bearingless Permanent Magnet Synchronous Motor using Independent Control - Normaisharah Mamat; Kasrul Abdul Karim; Zulkiflie Ibrahim; Tole Sutikno; Siti Azura Ahmad Tarusan; Auzani Jidin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Bearingless permanent magnet synchronous motor (BPMSM) combines the characteristic of the conventional permanent magent synchronous motor and magnetic bearing in one electric motor. BPMSM is a kind of high performance motor due to having both advantages of PMSM and magnetic bearing with simple structure, high efficiency, and reasonable cost. The research on BPMSM is to design and analyse BPMSM by using Maxwell 2-Dimensional of ANSYS Finite Element Method (FEM). Independent suspension force model and bearingless PMSM model are developed by using the method of suspension force. Then, the mathematical model of electromagnetic torque and radial suspension force has been developed by using Matlab/Simulink. The relation between force, current, distance and other parameter are determined. This research covered the principle of suspension force, the mathematical model, FEM analysis and digital control system of bearingless PMSM. This kind of motor is widely used in high speed application such as compressors, pumps and turbines.